Ultrasound-guided stellate ganglion block attenuates early postoperative visceral pain after laparoscopic hysterectomy: A prospective randomized controlled trial - Jing Lin; Yue Huang; Yaling Wen; Wanli Yang; Youbo Zuo (PLoS ONE, 2025)
Background Postoperative visceral pain remains a major challenge following laparoscopic hysterectomy. While stellate ganglion block (SGB) is increasingly utilized for acute and chronic pain management, limited evidence exists regarding its efficacy in modulating visceral pain after gynecologic laparoscopy. This study aimed to evaluate whether ultrasound-guided SGB could reduce early postoperative visceral pain intensity and opioid consumption. Methods In this prospective, randomized controlled trial, 90 patients undergoing laparoscopic hysterectomy were allocated (1:1:1) to receive ultrasound-guided SGB combined with transversus abdominis plane block (TAPB) (SGB group), TAPB alone (TAP group), or no nerve block (control group). The primary outcome was visceral pain intensity, assessed using visual analog scale (VAS) scores at rest and during movement at 1, 3, 6, 24, and 48 hours postoperatively. Secondary outcomes included rescue analgesia requirements and complications. Results The linear mixed-effects model revealed that the SGB group exhibited a significantly greater reduction in visceral pain intensity at rest and during movement at 1, 3, and 6 hours compared to the TAP and control groups ( P < 0.05). Notably, the percentage of patients requiring rescue analgesia was significantly lower in the SGB group compared to the TAP and control groups (14.3% vs. 32.1% and 48.1%, respectively, P < 0.05). No statistically significant differences in incisional pain were detected among the three groups at any time point ( P > 0.05). Conclusion Ultrasound-guided SGB effectively alleviates early postoperative visceral pain and reduces opioid demand, supporting its role as a valuable addition to multimodal analgesia protocols in laparoscopic hysterectomy.